On One Class of the Infinite Non-Abelian Groups - Tomanek, Ludovit; Tomankova, Anna (Communications - Scientific Letters of the University of Zilina, 2010)
We present some properties of one class of the infinite non-abelian groups. We deal with a generalization of the INH and KI groups. Our main results are Theorem 1, 2, 3 and Theorem 4.
Keywords: a group; a commutator of group; a locally graded group; p-quasicyclic group; a direct and semidirect product of groups; an extension of the group